Slovenski prevod Mednarodnih smernic za s šolo povezano sedentarno vedenje otrok in mladostnikov - Kastelic, Kaja (Šport (Ljubljana), 2024)
Many children and youth are excessively sedentary at school as well as outside of school. Studies have showed that higher levels of time spent in sedentary behaviour present a risk factor for health and healthy development of children and youth. The aim of this study is to present the process of translating the International school-related sedentary behaviour recommendations for children and youth into the Slovenian language, and to present the novel recommendations to the broader professional public in Slovenia. The translation process consisted of eight steps and included three experts (from the field of kinesiology and physiotherapy), a professional translator, the leading author of the recommendations, and a proofreader. The result of this process is the Slovenian translation of the recommendations that consists of the preamble, a glossary of terms, school-related sedentary behaviour recommendations, and implementation strategies. School environments offer an important opportunity to influence students’ movement behaviours and thereby their health and well-being. Recommendations for school-related sedentary behaviour provide guidance on planning and implementing actions for enhancing health and well-being of school-aged students. We have recognised that the novel recommendations meaningfully complement the existing national recommendations for movement behaviours of children and youth.
Keywords: dijaki; gibalni odmor; guidelines; movement break; priporočila; pupils; sedenje; sedentariness; sedentarnost; sitting; sport; students; šport; učenci